Dose effects of caffeine on testosterone and cortisol responses to resistance exercise - Beaven, C. M.; Hopkins, W. G.; Hansen, K. T.; Wood, M. R.; Cronin, J. B.; Lowe, T. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2008)
Introduction: Interest in the use of caffeine as an ergogenic aid has increased since the International Olympic Committee lifted the partial ban on its use. Caffeine has beneficial effects on various aspects of athletic performance, but its effects on training have been neglected. Purpose: To investigate the acute effect of caffeine on the exercise-associated increases in testosterone and cortisol in a double-blind crossover study. Methods: Twenty-four professional rugby-league players ingested caffeine doses of 0, 200, 400, and 800 mg in random order 1 hr before a resistance-exercise session. Saliva was sampled at the time of caffeine ingestion, at 15-min intervals throughout each session, and 15 and 30 min after the session. Data were log-transformed to estimate percent effects with mixed modeling, and effects were standardized to assess magnitudes. Results: Testosterone concentration showed a small increase of 15% (90% confidence limits, ± 19%) during exercise. Caffeine raised this concentration in a dose-dependent manner by a further small 21% (± 24%) at the highest dose. The 800-mg dose also produced a moderate 52% (± 44%) increase in cortisol. The effect of caffeine on the testosterone:cortisol ratio was a small decline (14%; ± 21%). Conclusion: Caffeine has some potential to benefit training outcomes via the anabolic effects of the increase in testosterone concentration, but this benefit might be counteracted by the opposing catabolic effects of the increase in cortisol and resultant decline in the testosterone:cortisol ratio.